The Implementation of Student Character Model at Public High Schools In Tanjungbalai City - Khairi, Ahmad Muammar; Ananda, Rusydi; Sitorus, Ahmad Syukri (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This research examines the implementation of the student character development model based on the Pancasila Student Profile Project (P5) in State Senior High Schools in Tanjungbalai. The study finds that the character development model utilizes Problem-Based Learning, Project-Based Learning, and Discovery Learning approaches, highlighting the importance of developing the Operational Curriculum for Educational Units to maximize students' potential. The implementation is integrated across subjects, significant event programs, and P5 projects, aiming to instill values such as religious devotion, global diversity, cooperation, independence, critical thinking, and creativity. This research employs a qualitative field research method to explore the implementation of the student character development model based on the Pancasila Student Profile Project (P5) in State Senior High Schools in Tanjungbalai. However, several challenges impede effective implementation, including a lack of understanding and support for P5, limited resources, diverse interpretations of Pancasila, difficulties in content delivery, and inadequate monitoring and evaluation processes. These challenges underscore the necessity for enhanced understanding, resource allocation, and comprehensive evaluation to optimize the P5 implementation and ensure the successful character development of students. The findings emphasize the need for strong collaboration among government, schools, teachers, students, and the community to overcome these challenges and achieve the intended educational goals.